MULTIMODALITY THERAPY FOR OSTEOSARCOMA OF THE STERNUM WITH RECONSTRUCTION OF COMPLEX CHEST WALL DEFECTS - V. E. Ivanov; A. A. Kurilchik; Yu. A. Ragulin; A. A. Zheravin; A. L. Starodubtsev; A. L. Zubarev (Сибирский онкологический журнал, 2017)
Background. Osteosarcoma is a high-grade malignant bone tumor that accounts for up to 6 % of all bone neoplasms. There are only a few published cases of primary sternal osteosarcomas, reflecting the rarity of these tumors. Recently, there has been a growing interest in performing radical excisions of chest wall tumors followed by combined single-stage reconstruction of the rib cage with implants made of biologically compatible materials. Material and methods. We present the case of a 49-year-old woman diagnosed with osteosarcoma of the sternum. The patient received a combined modality treatment including chemotherapy, radiotherapy and surgery. Titanium nickelid implants were used for the reconstruction of chest wall defects. Results. The multimodality treatment with reconstruction of postoperative chest wall defects allowed the achievement of the optimal quality of life for 21 months in the patient with very poor prognosis. Conclusion. The chest wall reconstruction using biocompatible materials from titanium nickelid appeared to be an effective and safe technique for the treatment of chest wall tumors.